A Review of the Aims and Principles of Guidance Activities in Schools - Recep Bilgin; Yunus Yildiz; Ayse Yildiz (International Journal of Social Sciences & Educational Studies, 2022)
Guidance is the activities carried out by experts to find solutions to people’s problems and support their developmental processes. In order for these activities to be carried out correctly, some principles and objectives must be taken into account. The fact that all people need help in their developmental processes and that each person is a case is the most important principle of guidance. All activities are shaped around this principle. With the adoption of this principle, the help people need can be given more effectively. In addition, preparing people for the future as the modern world needs is the foremost aim of guidance.